AB0262 Predictors of Patient Support Program Use Among Patients with Rheumatoid Arthritis. (9th June 2015) - van den Bosch, F.; Wassenberg, S.; Ostor, A.; Varothai, N.; Kalabic, J.; Garg, V.
Abstract : Background: The adalimumab (ADA) patient (pt) support program (PSP) is offered to pts with rheumatoid arthritis (RA). Evidence to understand factors affecting the use of PSPs is scarce. Objectives: To assess predictors of ADA PSP utilization among RA pts who initiate ADA treatment. Methods: This was a post hoc interim analysis of the Post-Marketing Observational Study to Determine the Effectiveness and Patient Satisfaction With Adalimumab Treatment in Patients With RA (PASSION; NCT01383421 ). In this multi-country, ex-US study, the PSP includes "Core elements" (starter pack, call center/hotline, nursing services, educational material, and injection guide; offered in all participating countries) and "other elements" (eg, refill reminders, email, newsletters, support groups, home delivery, and financial assistance; vary by country). PSP utilization (yes/no) was a dependent variable in a multivariate logistic regression model examining the following potential predictors of using the ADA PSP: baseline (BL) Patient Activation Measure-13 (PAM-13 1 ; evaluates knowledge, skills, and confidence essential to a pt managing his/her own health; scores classified a priori into 4 levels [higher level means greater pt involvement in disease management]), age, sex, race, RA disease duration, prior use of biologic disease-modifying anti-rheumatic drug (DMARD), Health Assessment Questionnaire Disability Index (HAQ-DI), BL Simplified Disease Activity Index (SDAI), and BL 28-joint Disease Activity Score based on C-reactive protein (DAS28(CRP)). Results: Most enrolled pts were female and white (Table ); BL characteristics were similar across the 4 PAM-13 levels. Overall, 427 of enrolled pts (51%) utilized the PSP, including 40%, 53%, 52%, and 58% of pts in PAM-13 Levels 1–4, respectively. Pts utilizing Core PSP elements but not other elements (n=93) included 19%, 14%, 9%, and 5% of pts in PAM-13 Levels 1–4, respectively. The percentages of pts utilizing both Core and Other PSP elements (n=292) increased with PAM-13 level and included 19%, 32%, 37%, and 48% of pts in PAM-13 Levels 1–4, respectively, suggesting greater overall PSP usage by pts in higher PAM-13 levels. Pts in Level 4 had the highest use for all Core PSP elements, including ADA call center (39%), educational material (41%), material regarding ADA (41%), ADA injection guide (39%), starter pack (32%), and nursing services (32%). Predictors favoring PSP use among observed RA pts included PAM-13 level (odds ratio [OR] per 1-level increase, 1.32; 1.12–1.55), white race (OR, 3.83; 95% CI, 2.04–7.20), prior use of biologic DMARDs (OR, 2.31; 95% CI, 1.46–3.65), BL HAQ-DI (OR, 1.37; 95% CI, 1.05–1.79), and BL DAS28(CRP) (OR, 1.18; 95% CI, 1.02–1.38). Female sex was a predictor for not using the PSP (OR, 0.62; 95% CI, 0.42–0.92) in this mostly female population. Conclusions: In pts with moderate to severe RA treated per standard of care, white race, prior biologic use, and BL disease parameters were positive predictors favoring PSP use. References: Hibbard JH, et al. Health Serv Res. 2004;39(4 Pt 1):1005-1026. Acknowledgements: AbbVie funded the study and the analysis, and approved the abstract for submission. Medical writing assistance was provided by Katherine Groschwitz and Michael Theisen of Complete Publication Solutions, LLC, and was supported by AbbVie. Disclosure of Interest: F. Van Den Bosch Consultant for: received speaker and/or consultancy fees from AbbVie, Celgene, Janssen, Novartis, Pfizer, and UCB, S. Wassenberg Grant/research support from: participated in phase 3 and phase 4 studies sponsored by AbbVie, Speakers bureau: received speakers honoraria of less than 5.000 € in the last 2 years from AbbVie; also received support, including speaker and/or consultancy fees and attendance at conferences, from Chugai, Janssen, MSD, Novartis, Pfizer, Roche, and UCB, A. Ostor Grant/research support from: received support from (including attendance at conferences), undertakes clinical trials and acts as a consultant to Roche, Chugai, MSD, AbbVie, Pfizer, Novartis, Napp, and BMS, N. Varothai Shareholder of: AbbVie, Employee of: AbbVie, J. Kalabic Shareholder of: AbbVie, Employee of: AbbVie, V. Garg Shareholder of: AbbVie, Employee of: AbbVie